A method for determining critical swimming velocity - Takahashi, S.; Wakayoshi, K.; Hayashi, A.; Sakaguchi, Y.; Kitagawa, K. (International Journal of Sports Medicine, 2009)
The purpose of this study was to determine whether the critical swimming velocity (Vcri) estimated by the swimming velocity for a distance of 300 m at maximal effort breaststroke reflects the maximal lactate steady state (MLSS). Twelve trained swimmers swam 50 m, 300 m and 2 000 m at maximal effort for determination of Vcri that averaged 1.167 ± 0.045 m · sec-1. Since Vcri was equivalent to 90.5 % of the mean swimming velocity over the distance of 300 m at maximal effort, the swimming velocity obtained by multiplying the swimming velocity for the distance of 300 m of each subject by 90.5 % was taken to be 100 % of the predicted critical swimming velocity (Vcri-pred). Then, in an MLSS test, the subjects were instructed to swim breaststroke 2 000 m (5 × 400 m) at three constant velocities (98 %, 100 %, and 102 % of Vcri-pred), interrupted by four short rest periods from 30 to 45 seconds for blood sampling and heart rate measurement. As a result, the blood lactate concentration at 100 % Vcri-pred showed a higher steady state than the slow velocity, but at high velocity did not show the steady state. In conclusion, we can accurately estimate the Vcri for breaststroke by a one-time 300-m maximal effort swimming test.